Design of a gelatin microparticle-containing self-microemulsifying formulation for enhanced oral bioavailability of dutasteride - Baek I; Ha ES; Yoo JW; Jung Y; Kim MS (Dove Medical Press, 2015)
In-hwan Baek,1,* Eun-Sol Ha,2,* Jin-Wook Yoo,2 Yunjin Jung,2 Min-Soo Kim21College of Pharmacy, Kyungsung University, 2College of Pharmacy, Pusan National University, Busan, Republic of Korea*These authors contributed equally to this workAbstract: In this study, a gelatin microparticle-containing self-microemulsifying formulation (SMF) was developed using a spray-drying method to enhance the oral delivery of the poorly water-soluble therapeutic dutasteride. The effect of the amount of gelatin and the type and amount of hydrophilic additives, namely, Gelucire® 44/14, poloxamer 407, sodium lauryl sulfate, Soluplus®, Solutol™ HS15, and D-α-tocopheryl polyethylene glycol 1000 succinate, on the droplet size, dissolution, and oral absorption of dutasteride from the SMF was investigated. Upon dispersion of the gelatin microparticle-containing SMF in water after spray-drying, the mean droplet size of the aqueous dispersion was in the range of 110–137 nm. The in vitro dissolution and recrystallization results showed that gelatin could be used as a solid carrier and recrystallization inhibitor for the SMF of dutasteride. Furthermore, combination of the gelatin microparticle-containing SMF and Soluplus enhanced the dissolution properties and oral absorption of dutasteride. The results of our study suggest that the gelatin microparticle-containing SMF in combination with Soluplus could be useful to enhance the oral absorption of dutasteride.Keywords: dissolution, solubility, bioavailability, dutasteride